Anaerobic Dehalogenation of Hydroxylated Polychlorinated Biphenyls by Desulfitobacterium dehalogenans - Wiegel, Juergen (American Society for Microbiology, 1999)
Ten years after reports on the existence of anaerobic dehalogenation of polychlorinated biphenyls (PCBs) in sediment slurries, we report here on the rapid reductive dehalogenation of para-hydroxylated PCBs (HO-PCBs), the excreted main metabolites of PCB in mammals, which can exhibit estrogenic and antiestrogenic activities in humans. The anaerobic bacterium Desulfitobacterium dehalogenans completely dehalogenates all flanking chlorines (chlorines in ortho position to the para-hydroxyl group) from congeners such as 3,3′,5,5′-tetrachloro-4,4′-dihydroxybiphenyl.